THE DIFFERENCE IN THE EFFECT OF FIGURE EIGHT WRAPS AROUND AND FIGURE EIGHT DRIBBLE EXERCISES ON THE DRIBBLE SKILLS OF DM BASKETBALL CLUB BASKETBALL PLAYERS IN 2025 - Harahap, Fadlan; Supriadi, Amir; Sitepu, Indra Darma (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Dribbling is one of the fundamental skills in basketball and is especially important for beginner players, as it plays a major role in overall game control. Observations of athletes at DM Basket Club revealed several problems, including low dribbling ability, stiff movements, excessive focus on the ball, poor ball control and direction, as well as suboptimal coordination and agility. These conditions cause athletes to have difficulty avoiding opponents and to easily lose ball possession during games. This study aimed to determine the differences in the effects of figure eight wraps around training and figure eight dribble training on the dribbling skills of DM Basket Club basketball players in 2025. The study employed a quantitative experimental method with a pre-test and post-test two-group design using matching pairing. The population and sample consisted of 12 athletes selected through total sampling. Data analysis was conducted using normality tests, homogeneity tests, and t-tests. The results showed that both figure eight wraps around training and figure eight dribble training had a significant effect on improving athletes’ dribbling skills. However, there was no significant difference in the effect between the two types of training, indicating that both training methods are equally effective in enhancing the dribbling skills of DM Basket Club basketball players.